Performance Evaluation of Broad Band CDMA Signal Using Beam Forming Antenna Technology for Next Generation Communications - Javaid A Sheikh (Institute of Advanced Engineering and Science, 2015)
In order to accommodate various multimedia services, next generation wireless networks are characterized by very high transmission rates. Thus, in such systems and networks, the received signal is not only limited by noise like Additive White Gaussian noise (AWGN) but especially with increasing data transmission rate by the Intersymbol Symbol Interference (ISI) due to time dispersion of channel. A number of techniques such as rake receiver in CDMA systems and equalizers in GSM systems have been proposed to combat the effect of fading so as to improve the performance of wireless communication network. In this paper we evolve the performance of uncoded uplink transmission in broadband CDMA using beam forming technique under multipath conditions. The beam-former has been implemented using Transport Delay Line (TDL) filters. An expression for the optimal weights of a TDL based beam former has been derived. A carrier frequency of 2 Ghz has been used in this work as they are useful for next generation wireless systems. Simulation results show that TDL beamformer can reduce the multipath fading and Multiple Access Interferance (MAI). It has been shown that if SNR (related with Variance of the channel) is maintained at 10 db and if a 3 ray based beamformer having 3 antennas with 3 taps is used, the Error Rate of 0.1was found without using channel coding.